Psychometric properties of the apathy evaluation scale in patients with Parkinson's disease. Issue 4 (18th April 2017) - Lueken, Ulrike; Evens, Ricarda; Balzer‐Geldsetzer, Monika; Baudrexel, Simon; Dodel, Richard; Gräber‐Sultan, Susanne; Hilker‐Roggendorf, Rüdiger; Kalbe, Elke; Kaut, Oliver; Mollenhauer, Brit; Reetz, Kathrin; Schäffer, Eva; et al.
Abstract: Parkinson's disease (PD) frequently entails non‐motor symptoms, worsening the course of the disease. Apathy is one of the core neuropsychiatric symptoms that has been investigated in recent years; research is however hampered by the limited availability of well‐evaluated apathy scales for these patients. We evaluated the psychometric properties of the Apathy Evaluation Scale (AES) in a sample of PD patients. Psychometric properties, convergent and discriminant validity and sensitivity/specificity were evaluated in patients with ( n  = 582) or without dementia/depression ( n  = 339). Internal consistency was high in the entire sample as well as in patients without dementia/depression. Correlations were moderate for convergent validity (UPDRS I item 4: motivation). While apathy could be differentiated from cognitive decline, it was related to depression (Geriatric Depression Scale, GDS‐15). The overall classification accuracy based on the UPDRS I item 4 was comparable for AES and GDS scores. The AES exhibits good psychometric properties in PD patients with and without dementia and/or depression. Commonly used screenings on the presence of apathy had low detection rates compared to the AES and reflected both apathetic and depressive symptoms. Psychometric evaluation of available instruments will support further research on the clinical relevance of apathy for disease progression and treatment approaches in PD patients.